OPTIMALISASI PERAN LANUD SOEWONDO TERHADAP PERTAHANAN UDARA INDONESIA - Wulandari, Tsaniyah; Heri Budi Wibowo; Mas Ayu Elita Hafizah; Y.H. Yogaswara (CV. AFDIFAL MAJU BERKAH, 2023)
Soewondo Air Force Base (AFB) has an important role in maintaining the surrounding airspace's security, including securing the Soewondo Air Force assignment area from various threats that could potentially occur and threaten national sovereignty. Increasing the ability of air defense. needs to be done through an analysis of optimizing the role of the Soewondo air force base for Indonesia's air defense. The research was conducted using a qualitative method with sources of information obtained from the Commander of Soewondo air force base and a literature study. Soewondo air force base plays a role in Indonesia's defense as an airbase that has a strategic role in maintaining the security of the North Sumatra region and its surroundings. The limited capabilities and available weapon systems still hinder airspace surveillance. Cooperation and coordination between Soewondo air force base and relevant agencies are needed to maintain air security in North Sumatra and its surroundings and strengthen the weapon systems for optimal operation in air defense and safeguarding national sovereignty, particularly in securing vital national objects. Relocating Soewondo air force base to type A classification equipped with modern weapon systems, such as the Oerlikon Skyshield missile, and utilizing technologies like the QW-3 manpads missile, UAV for intelligence and surveillance missions, are crucial steps in achieving optimal air defense for Indonesia